Reimplantation of Accidentally Avulsed Permanent Maxillary Anterior Teeth in a 10-Year-Old Girl - Sheikh, Md Abdul Hannan (Journal of Enam Medical College, 2017)
Accidental tooth avulsion is a grievous injury and common among the children. Management of avulsed tooth within alveolar socket by reimplantation becomes a challenge for the clinician due to extraoral time and media of transportation. Although the long-term prognosis of reimplantation is poor, the time during which the tooth remain within the arch will guide the development of alveolar bone completely. Moreover, reimplantation will maintain anatomical, functional and esthetic rehabilitation of the patient. In this case report, we present a case of accidental avulsion where teeth were gently rinsed of any debris and placed in normal saline during the examination and preparation of the reimplantation sockets. The teeth were then reimplanted, functionally splinted followed by endodontical treatment. After 12 months follow-up the periodontal space was healed perfectly without any resorption or ankylosis. J Enam Med Col 2017; 7(3): 165-169